Efficient antibacterial modified chitosan-nano-copper composite gel and preparation method thereof

Through the synergistic effect of modified chitosan and nano-copper composite gel, the problem of prone to failure of antibacterial activity of nano-silver copper particles is solved, and efficient and stable antibacterial effect is achieved, and the dispersion and stability of nano-copper are improved. , suitable for sewage treatment.

CN119119662APending Publication Date: 2024-12-13CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411307617.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-13

Smart Images

  • Figure BDA0005049724240000011
    Figure BDA0005049724240000011
  • Figure BDA0005049724240000041
    Figure BDA0005049724240000041
  • Figure BDA0005049724240000042
    Figure BDA0005049724240000042
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, in particular to efficient antibacterial modified chitosan-nano-copper composite gel and a preparation method thereof. Nano-copper particles have a good antibacterial effect, but the antibacterial activity of the nano-copper particles in the application process is prone to losing efficacy. Aiming at the problems, the invention provides the efficient antibacterial modified chitosan-nano-copper composite gel, the C-6 position in the molecular structure of chitosan in the formula is chemically modified, the water solubility and dispersity of the obtained modified chitosan are remarkably improved, and the obtained modified chitosan is used as a synergistic antibacterial agent of nano-copper particles, so that the antibacterial property of the nano-copper particles is improved, and the antibacterial property of the nano-copper particles is improved. The antibacterial property and the antibacterial stability of the composite gel are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment, and in particular to a highly efficient antibacterial modified chitosan-nano copper composite gel and a preparation method thereof. Background Art

[0002] Microbial pollution in water refers to the presence of pathogenic microorganisms (such as bacteria, parasites, etc.) in water that exceeds environmental quality indicators, thus causing harm to human health and aquatic ecosystems. In order to reduce the impact on the environment, sewage must be effectively treated before discharge.

[0003] Nano copper has an inhibitory effect on a variety of bacteria, fungi, viruses and other microorganisms. Compared with other metal nanoparticles, nano copper has low toxicity and less impact on humans and the environment. However, due to its high activity, nano copper particles are prone to agglomeration and oxidation, thus losing their antibacterial activity, which greatly limits their application.

[0004] In order to expand the application field of nano copper particles, the present invention provides a composite gel with nano copper and modified chitosan as antibacterial agents, which can improve the dispersibility of nano copper and reduce its oxidation, and through the synergistic effect of modified chitosan and nano copper, the composite gel has high antibacterial efficiency and good stability. Summary of the invention

[0005] The problem in the prior art is that nano copper particles have good antibacterial effect, but their antibacterial activity is easily lost during application. In view of the above problems, the present invention provides a highly effective antibacterial modified chitosan-nano copper composite gel, which comprises the following raw material components by weight:

[0006]

[0007] The polyvinyl alcohol-soy protein isolate solution is prepared according to the following steps:

[0008] Add polyvinyl alcohol to distilled water, then place in a water bath at 80-95° C. and stir until the polyvinyl alcohol is completely dissolved, and cool to room temperature to obtain a PVA solution, then add soy protein isolate to the PVA solution, stir and mix evenly to obtain a polyvinyl alcohol-soy protein isolate solution, wherein the mass concentration of the polyvinyl alcohol in the distilled water is 2%, and the mass ratio of the soy protein isolate to the polyvinyl alcohol is 1:1,

[0009] The modified chitosan solution is a solution formed by completely dissolving the modified chitosan in an acetic acid aqueous solution, wherein the mass concentration of the modified chitosan in the acetic acid aqueous solution is 2%.

[0010] The mass concentration of the acetic acid aqueous solution is 2%,

[0011] The modified chitosan is composed of sulfated chitosan and phosphorylated chitosan in a mass ratio of 1:1.

[0012] The preparation method of the nano copper particle solution is as follows:

[0013] (1) grinding the dried dandelion flowers with a grinder, passing the obtained dandelion flower powder through a 60-mesh sieve for later use, then adding the dandelion flower powder to an 80% ethanol aqueous solution, ultrasonically dispersing the dandelion flower powder at 60° C., cooling the dandelion flower powder to room temperature, filtering the dandelion flower powder with a filter paper, and obtaining a dandelion flower extract, wherein the mass concentration of the dandelion flower powder in the ethanol aqueous solution is 4%;

[0014] (2) CuSO4·5H2O was dissolved in 100 mL of deionized water to obtain a copper sulfate solution with a mass concentration of 10 mg / mL, and the dandelion flower extract obtained in step (1) was mixed with the copper sulfate solution in a volume ratio of 9:1. The reaction system was then placed in a water bath at 80° C. and stirred to react to generate a black precipitate. After the reaction was completed, the temperature of the reaction system was cooled to room temperature to obtain a nano copper particle solution.

[0015] Preferably, the preparation method of the sulfated chitosan is as follows:

[0016] (1) Mix 3-5 g of chitosan with 5 mL of dichloroacetic acid and 50 mL of formamide at 50° C. to prepare a chitosan solution;

[0017] (2) 10 mL of chlorosulfonic acid and 50 mL of N,N-dimethylformamide were mixed evenly and kept in an ice bath for 1 h to obtain a sulfonation reagent;

[0018] (3) The chitosan solution and the sulfonation reagent were mixed uniformly in a volume ratio of 1:1, and stirred at 70°C for 5-6 hours. After the reaction was completed, anhydrous ethanol was added to the reaction solution for precipitation, and the mixture was allowed to stand for 12 hours and filtered. The obtained solid product was washed several times with anhydrous ethanol, dissolved in deionized water, and the pH of the solution was adjusted to neutral with sodium bicarbonate aqueous solution, and then dialyzed with dialysis tape. After freeze-drying, a white solid was obtained, which was sulfated chitosan.

[0019] Preferably, the concentration of the sodium bicarbonate aqueous solution is 0.1-0.5M.

[0020] Preferably, the preparation method of the phosphorylated chitosan is as follows:

[0021] 3-5g of chitosan is evenly dispersed in methanesulfonic acid, and then 2g of phosphorus pentoxide is slowly added. The reaction system is then placed in an ice-water mixture for 1 hour, during which it is stirred every 5 minutes. The reaction solution is then washed three times with ether, acetone and methanol, respectively, and finally, freeze-dried to obtain phosphorylated chitosan, wherein the mass volume ratio of chitosan to methanesulfonic acid is 1:7.

[0022] Preferably, the method for preparing the highly effective antibacterial modified chitosan-nano copper composite gel comprises the following steps:

[0023] According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.

[0024] The present invention has the following beneficial effects:

[0025] (1) The composite gel obtained by the present invention uses polyvinyl alcohol and soy protein as carriers, has good biocompatibility and degradability, and reduces the impact on the environment. At the same time, polyvinyl alcohol and soy protein isolate can be used as dispersants to help the nano copper particles to be evenly dispersed in the gel matrix, reduce the aggregation and sedimentation between particles, thereby improving the stability of nano copper and enabling the composite gel to exert an excellent antibacterial effect;

[0026] (2) The present invention chemically modifies the C-6 position in the chitosan molecular structure, significantly improving the water solubility and dispersibility of the obtained modified chitosan (including phosphorylated chitosan and sulfated chitosan). The obtained modified chitosan is used as a synergistic antibacterial agent for nano-copper particles, further improving the antibacterial properties of the composite gel;

[0027] (3) The present invention uses dandelions discarded from pharmaceutical processing as a green in-situ reducing agent, which has the advantages of low cost and environmental friendliness;

[0028] (4) The modified chitosan in the modified chitosan solution of the present invention has active groups such as amino and hydroxyl groups in its structure that can form stable coordination bonds with nano-copper particles. This bonding action can greatly improve the dispersibility and stability of the nano-copper particles, and further improve the antibacterial effect and antibacterial stability of the composite gel. DETAILED DESCRIPTION

[0029] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0030] The chitosan in the following embodiments of the present invention is high deacetylation chitosan (DD%: 80.0%-95%), purchased from Sinopharm Chemical Reagent Co., Ltd., with the product number 20200922.

[0031] The polyvinyl alcohol-soy protein isolate solution in the following embodiments of the present invention is prepared according to the following steps:

[0032] Add polyvinyl alcohol to distilled water, then place in a water bath at 80°C and stir until the polyvinyl alcohol is completely dissolved, and cool to room temperature to obtain a PVA solution, then add soy protein isolate to the PVA solution, stir and mix evenly to obtain a polyvinyl alcohol-soy protein isolate solution, wherein the mass concentration of the polyvinyl alcohol in the distilled water is 2%, and the mass ratio of the soy protein isolate to the polyvinyl alcohol is 1:1,

[0033] The modified chitosan solution in the following embodiments of the present invention is a solution formed by completely dissolving the modified chitosan in an acetic acid aqueous solution, wherein the mass concentration of the modified chitosan in the acetic acid aqueous solution is 2%, the mass concentration of the acetic acid aqueous solution is 2%, and the modified chitosan is composed of sulfated chitosan and phosphorylated chitosan in a mass ratio of 1:1.

[0034] The nano copper particle solution in the following embodiments of the present invention is prepared as follows:

[0035] (1) grinding the dried dandelion flowers with a grinder, passing the obtained dandelion flower powder through a 60-mesh sieve for later use, then adding the dandelion flower powder to an 80% ethanol aqueous solution, ultrasonically dispersing the dandelion flower powder at 60° C., cooling the dandelion flower powder to room temperature, filtering the dandelion flower powder with a filter paper, and obtaining a dandelion flower extract, wherein the mass concentration of the dandelion flower powder in the ethanol aqueous solution is 4%;

[0036] (2) CuSO4·5H2O was dissolved in 100 mL of deionized water to obtain a copper sulfate solution with a mass concentration of 10 mg / mL, and the dandelion flower extract obtained in step (1) was mixed with the copper sulfate solution in a volume ratio of 9:1. The reaction system was then placed in a water bath at 80° C. and stirred to react to generate a black precipitate. After the reaction was completed, the temperature of the reaction system was cooled to room temperature to obtain a nano copper particle solution.

[0037] The sulfated chitosan in the following embodiments of the present invention is prepared as follows:

[0038] (1) 4 g of chitosan was mixed with 5 mL of dichloroacetic acid and 50 mL of formamide at 50° C. to prepare a chitosan solution;

[0039] (2) 10 mL of chlorosulfonic acid and 50 mL of N,N-dimethylformamide were mixed evenly and kept in an ice bath for 1 h to obtain a sulfonation reagent;

[0040] (3) The chitosan solution and the sulfonation reagent were mixed uniformly in a volume ratio of 1:1, and stirred at 70°C for 5-6 hours. After the reaction was completed, anhydrous ethanol was added to the reaction solution for precipitation, and the mixture was allowed to stand for 12 hours and filtered. The obtained solid product was washed several times with anhydrous ethanol, dissolved in deionized water, and the pH of the solution was adjusted to neutral with a 0.5M sodium bicarbonate aqueous solution. The solution was then dialyzed with a dialysis tape and freeze-dried to obtain a white solid, which was sulfated chitosan.

[0041] The phosphorylated chitosan in the following embodiments of the present invention is prepared as follows:

[0042] 4 g of chitosan was evenly dispersed in methanesulfonic acid, and then 2 g of phosphorus pentoxide was slowly added. The reaction system was then placed in an ice-water mixture for 1 hour, during which it was stirred every 5 minutes. The reaction solution was then washed three times with ether, acetone and methanol, respectively, and finally, freeze-dried to obtain phosphorylated chitosan, wherein the mass volume ratio of chitosan to methanesulfonic acid was 1:7.

[0043] Example 1

[0044] A highly effective antibacterial modified chitosan-nano copper composite gel, the raw material components of which are as follows in parts by weight:

[0045]

[0046] The preparation method of the highly effective antibacterial modified chitosan-nano copper composite gel is as follows:

[0047] According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.

[0048] Example 2

[0049] A highly effective antibacterial modified chitosan-nano copper composite gel, the raw material components of which are as follows in parts by weight:

[0050]

[0051]

[0052] The preparation method of the highly effective antibacterial modified chitosan-nano copper composite gel is as follows:

[0053] According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.

[0054] Example 3

[0055] A highly effective antibacterial modified chitosan-nano copper composite gel, the raw material components of which are as follows in parts by weight:

[0056]

[0057] The preparation method of the highly effective antibacterial modified chitosan-nano copper composite gel is as follows:

[0058] According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.

[0059] Example 4

[0060] A highly effective antibacterial modified chitosan-nano copper composite gel, the raw material components of which are as follows in parts by weight:

[0061]

[0062] The preparation method of the highly effective antibacterial modified chitosan-nano copper composite gel is as follows:

[0063] According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.

[0064] Example 5

[0065] A highly effective antibacterial modified chitosan-nano copper composite gel, the raw material components of which are as follows in parts by weight:

[0066]

[0067] The preparation method of the highly effective antibacterial modified chitosan-nano copper composite gel is as follows:

[0068] According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.

[0069] Comparative Example 1 is the same as Example 1, except that the modified chitosan solution in Comparative Example 1 is a solution formed by completely dissolving the modified chitosan in an acetic acid aqueous solution, the mass concentration of the modified chitosan in the acetic acid aqueous solution is 2%, the mass concentration of the acetic acid aqueous solution is 2%, and the modified chitosan is entirely sulfated chitosan.

[0070] Comparative Example 2 is the same as Example 1, except that the modified chitosan solution in Comparative Example 2 is a solution formed by completely dissolving the modified chitosan in an acetic acid aqueous solution, the mass concentration of the modified chitosan in the acetic acid aqueous solution is 2%, the mass concentration of the acetic acid aqueous solution is 2%, and the modified chitosan is entirely phosphorylated chitosan.

[0071] Comparative Example 3 is the same as Example 1, except that the preparation method of the nano copper particle solution in Comparative Example 3 is as follows:

[0072] CuSO4·5H2O was dissolved in 100 mL of deionized water to obtain a copper sulfate solution with a mass concentration of 10 mg / mL, and the reducing agent solution and the copper sulfate solution were mixed in a volume ratio of 9:1. The reaction system was then placed in a water bath at 80° C. and stirred to react to generate a black precipitate. After the reaction was completed, the temperature of the reaction system was cooled to room temperature to obtain a nano copper particle solution, wherein the reducing agent solution was an aqueous solution of sodium citrate with a mass concentration of 4%.

[0073] Comparative Example 4 is the same as Example 1, except that the polyvinyl alcohol-soy protein isolate solution in Comparative Example 4 is prepared according to the following steps:

[0074] Polyvinyl alcohol is added to distilled water, and then placed in a water bath at 80° C. and stirred until the polyvinyl alcohol is completely dissolved. After cooling to room temperature, a PVA solution is obtained. Then, soy protein isolate is added to the PVA solution, and stirred to mix evenly to obtain a polyvinyl alcohol-soy protein isolate solution, wherein the mass concentration of the polyvinyl alcohol in the distilled water is 2%, and the mass ratio of the soy protein isolate to the polyvinyl alcohol is 3:1.

[0075] Comparative Example 5 is the same as Example 1, except that the polyvinyl alcohol-soy protein isolate solution in Comparative Example 5 is prepared according to the following steps:

[0076] Polyvinyl alcohol is added to distilled water, and then placed in a water bath at 80° C. and stirred until the polyvinyl alcohol is completely dissolved. After cooling to room temperature, a PVA solution is obtained. Then, soy protein isolate is added to the PVA solution, and stirred to mix evenly to obtain a polyvinyl alcohol-soy protein isolate solution, wherein the mass concentration of the polyvinyl alcohol in the distilled water is 2%, and the mass ratio of the soy protein isolate to the polyvinyl alcohol is 1:3.

[0077] Performance Testing

[0078] The colonies of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa were picked and placed in LB liquid medium (yeast powder 5g / L, sodium chloride 10g / L, beef peptone 10 / L) and cultured at 37°C. When the viable bacterial concentration of the culture medium reached 1.0×10 8 cfu / mL, 0.1mL was respectively transferred and coated on different LB solid culture media (yeast powder 5g / L, sodium chloride 10g / L, beef peptone 10g / L, agar 20g / L), and a sterilized stainless steel punch was used to punch a circular hole with a diameter of 9.0mm on the LB solid culture medium, and then 0.3g of the gel obtained in Examples 1-5 and Comparative Examples 1-4 was respectively filled into the circular holes of different LB solid culture media, and placed in a 37°C incubator for 18h, and the diameters of the inhibition zones of different gels against Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa in LB solid culture media were measured using a ruler. The specific test results are shown in Table 1.

[0079] Table 1

[0080]

[0081] Gel recyclability test

[0082] The test method is as follows:

[0083] The colonies of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa were picked and placed in different LB liquid culture media (yeast powder 5g / L, sodium chloride 10g / L, beef peptone 10 / L) and cultured at 37°C. When the viable bacterial concentration of the culture medium reached 1.0×10 8 cfu / mL, add 0.3g of the composite gel obtained in Examples 1-5 to different LB liquid culture media, and continue to shake and culture for 1h. Then take out 0.1mL of the bacterial suspension, dilute it to 1000 times with 0.9% sterile saline, and calculate the antibacterial rate of the composite gel in water by the plate counting method. Take out the used composite gel from the bacterial suspension, carefully wash it with clean water and wipe off the surface moisture, repeat the above operation 10 times, analyze the effect of repeated use on the antibacterial effect of the gel, and judge the recycling ability of the gel. The test results are shown in Table 2.

[0084] Table 2

[0085]

[0086] Gel stability

[0087] The test method is as follows: the prepared composite gels obtained in Examples 1-5 are placed at room temperature and taken out every 15 days, with 0.3 g taken out each time. Colonies of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa are picked out and placed in different LB liquid culture media (yeast powder 5g / L, sodium chloride 10g / L, beef peptone 10 / L) and cultured at 37°C. When the viable bacterial concentration of the culture medium reaches 1.0×10 8 cfu / mL, 0.3g of the composite gel obtained in Examples 1-5 was added to different culture media and the culture was continued for 1h. Then 0.1mL of the bacterial suspension was taken out and diluted to a suitable concentration with 0.9% sterile saline, and the antibacterial rate of the composite gel in water was calculated by the plate count method. The above operation was repeated until the 45th day, and the stability of the composite gel was analyzed. The test results are shown in Table 3 and Table 3.

[0088] Table 3

[0089]

[0090] Table 3

[0091]

[0092] Gel compatibility

[0093] The test method is as follows:

[0094] The biocompatibility of the composite gels obtained in Examples 1-5 to PK-15 cells was detected by MTT colorimetry. The PK-15 cell suspension with an initial density of 6.5×105 / mL was inoculated into a 96-well plate. After incubation for 24 hours, the original culture medium was removed, and the composite gels obtained in Examples 1-5 were weighed in different masses and soaked in deionized water to obtain composite gel soaking solutions. The concentrations of the gel soaking solutions were 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, 5 mg / mL, and 10 mg / mL, respectively. After continuing to incubate for 24 hours, 10 μL of MTT solution was added to each well, incubated for 4 hours, and the supernatant was removed by centrifugation. 150 μL of DMSO solution was added to each well. The absorbance was quantified by a microplate reader at a wavelength of 570 nm. The OD value was positively correlated with the metabolic activity of the cells. The higher the cell activity, the better its biocompatibility. The test results are shown in Table 4 and Table 4.

[0095] Table 4

[0096]

[0097] Table 4

[0098]

[0099] Gel adsorption performance

[0100] The test method is as follows:

[0101] Deionized water was used to prepare a methylene blue (MB) solution with an initial concentration of 600 mg / L and a methyl orange (MO) solution with an initial concentration of 500 mg / L. 5 mL of the solutions with different initial concentrations were respectively measured and placed in screw-mouth bottles. 0.1 g of the gel material obtained in Examples 1-5 and Comparative Examples 1-5 was added to different screw-mouth bottles, respectively. The mixture was shaken at a constant temperature of 160 rpm at 35° C. until the dye adsorption equilibrium was reached. The supernatant was then taken out and diluted 20 times. The absorbance was measured in an ultraviolet spectrophotometer (the experiment was performed three times), and the adsorption rate of the adsorbent to the dye was calculated. The test results are shown in Table 5.

[0102] Table 5

[0103]

[0104] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A highly effective antibacterial modified chitosan-nano copper composite gel, It is characterized in that The raw materials are as follows, by weight: The polyvinyl alcohol-soy protein isolate solution is prepared according to the following steps: Add polyvinyl alcohol to distilled water, then place in a water bath at 80-95° C. and stir until the polyvinyl alcohol is completely dissolved, and cool to room temperature to obtain a PVA solution, then add soy protein isolate to the PVA solution, stir and mix evenly to obtain a polyvinyl alcohol-soy protein isolate solution, wherein the mass concentration of the polyvinyl alcohol in the distilled water is 2%, and the mass ratio of the soy protein isolate to the polyvinyl alcohol is 1:1, The modified chitosan solution is a solution formed by completely dissolving the modified chitosan in an acetic acid aqueous solution, wherein the mass concentration of the modified chitosan in the acetic acid aqueous solution is 2%. The mass concentration of the acetic acid aqueous solution is 2%, The modified chitosan is composed of sulfated chitosan and phosphorylated chitosan in a mass ratio of 1:

1. The preparation method of the nano copper particle solution is as follows: (1) grinding the dried dandelion flowers with a grinder, passing the obtained dandelion flower powder through a 60-mesh sieve for later use, then adding the dandelion flower powder to an 80% ethanol aqueous solution, ultrasonically dispersing the dandelion flower powder at 60° C., cooling the dandelion flower powder to room temperature, filtering the dandelion flower powder with a filter paper, and obtaining a dandelion flower extract, wherein the mass concentration of the dandelion flower powder in the ethanol aqueous solution is 4%; (2) CuSO 4 ·5H 2 O is dissolved in 100 mL of deionized water to obtain a copper sulfate solution with a mass concentration of 10 mg / mL, the dandelion flower extract obtained in step (1) is mixed with the copper sulfate solution in a volume ratio of 9:1, and then the reaction system is placed in a water bath at 80° C. and stirred to react to generate a black precipitate. After the reaction is completed, the temperature of the reaction system is cooled to room temperature to obtain a nano copper particle solution.

2. The highly effective antibacterial modified chitosan-nano copper composite gel according to claim 1, It is characterized in that The preparation method of the sulfated chitosan is as follows: (1) Mix 3-5 g of chitosan with 5 mL of dichloroacetic acid and 50 mL of formamide at 50° C. to prepare a chitosan solution; (2) 10 mL of chlorosulfonic acid and 50 mL of N,N-dimethylformamide were mixed evenly and kept in an ice bath for 1 h to obtain a sulfonation reagent; (3) The chitosan solution and the sulfonation reagent were mixed uniformly in a volume ratio of 1:1, and stirred at 70°C for 5-6 hours. After the reaction was completed, anhydrous ethanol was added to the reaction solution for precipitation, and the mixture was allowed to stand for 12 hours and filtered. The obtained solid product was washed several times with anhydrous ethanol, dissolved in deionized water, and the pH of the solution was adjusted to neutral with sodium bicarbonate aqueous solution, and then dialyzed with dialysis tape. After freeze-drying, a white solid was obtained, which was sulfated chitosan.

3. The highly effective antibacterial modified chitosan-nano copper composite gel according to claim 2, It is characterized in that The concentration of the sodium bicarbonate aqueous solution is 0.1-0.5M.

4. The highly effective antibacterial modified chitosan-nano copper composite gel according to claim 1, It is characterized in that The preparation method of the phosphorylated chitosan is as follows: 3-5g of chitosan is evenly dispersed in methanesulfonic acid, and then 2g of phosphorus pentoxide is slowly added. The reaction system is then placed in an ice-water mixture for 1 hour, during which it is stirred every 5 minutes. The reaction solution is then washed three times with ether, acetone and methanol, respectively, and finally, freeze-dried to obtain phosphorylated chitosan, wherein the mass volume ratio of chitosan to methanesulfonic acid is 1:

7.

5. The highly effective antibacterial modified chitosan-nano copper composite gel according to claim 1, It is characterized in that The preparation method comprises the following steps: According to the formula, the polyvinyl alcohol-soy protein isolate solution and the modified chitosan solution are mixed evenly, and the nano-copper particle solution is added while stirring. After mixing evenly, polyvinyl pyrrolidone is added to the mixed solution. After stirring evenly, glutaraldehyde is added, and stirring is continued until a gel is formed to obtain a highly efficient antibacterial modified chitosan-nano-copper composite gel.